Investigation of a Behavioural Model for Financial Decision Making - Pitcher, C (University of Oxford;Mathematics, 2008)
Many economic models assume that individuals make decisions by maximizing their expected utility. Expected utility theory was developed to explain the way people behave when faced with choices under risk and uncertainty. However, the explanatory power of this theory has come into question because of systematic violations that have been observed in practice. This paper summarizes these violations and analyses a new theoretical framework that was introduced to overcome these violations called prospect theory. This theory was first proposed by Kahneman and Tversky in 1979, but the theory was later modified to become cumulative prospect theory. The purpose of this paper is to examine this new theory and to apply its framework to the lottery market. The parameters of the functional form of cumulative prospect theory are estimated. A value function with rapidly diminishing sensitivity, and a decision weighting function that was essentially a step function is found. The implications of these results are examined, and these results are compared to estimates given in the literature.